Behavioral model modification theory of planned behavior considering factors of religiosity and awareness of purchasing halal cosmetics: a case study in yogyakarta - Linarti, Utaminingsih; Ulfa, Mulia (Universitas Ahmad Dahlan, 2021)
The assurance of the certainty of halal products needs to be considered, given the large Muslim population. Currently, the use of cosmetics is part of the main needs, this is indicated by the increasing growth rate of cosmetic sales in Indonesia. The behavior of purchasing cosmetic products with guaranteed halal product certainty is interesting to note. We can discuss the magnitude of the influence between product needs, religious principles, concerns, intentions, and behavior of Muslim consumers. The purpose of this study was to determine the factors that influence consumer intentions and behavior in buying halal cosmetic products using a modification of the Theory of Planned Behavior (TPB) model by considering the factors of religiosity and awareness. The results showed that attitudes, subjective norms, perception control, and religiosity had a positive and significant influence, while the awareness factor was not significant on consumer intentions to buy halal cosmetic products. While the intention has a positive and significant effect on the behavior of buying halal cosmetics.